Predictors of aspiration, lower respiratory tract infection, and respiratory failure among individuals with Rett Syndrome: analysis of real-world claims data in the United States - Rajagopalan, Krithika; Rashid, Nazia; Doshi, Dilesh; Gopal, Daksha (Frontiers in Pediatrics, 2025)
BackgroundRett (RTT) syndrome, a rare, neurodevelopmental disorder affects multiple organ-systems (i.e., gastrointestinal, respiratory), with diverse clinical manifestations. While gastrointestinal manifestations are well-known, respiratory manifestations [i.e., aspiration, lower respiratory tract infection (LRTI), and respiratory failure (RF)] and associated predictors are not well-studied. This real-world data analysis evaluated the predictors of aspiration, LRTI, and RF among RTT individuals in the United States.MethodsA retrospective database analysis using IQVIA's Anonymized Patient Level database from 08/01/2020 to 03/31/2023 was conducted to identify newly diagnosed RTT individuals with ≥1 RTT diagnostic claim (ICD-10-CM: F84.2) between 02/01/2021 and 03/31/2022. Index date was the first RTT diagnostic claim. Eligible sample included individuals with 6-months pre-index and 12-months post-index follow-up, as well as no pre-index cerebrovascular disease or brain trauma diagnosis. Predictors of aspiration, LRTI, and RF were separately evaluated using exploratory backward selection models followed by confirmatory multivariable logistic regressions and reported using odds ratios (OR) with 95% confidence intervals (95% CI).ResultsOf the 1,994 with RTT, 7.27% (n = 145), 9.48% (n = 189), and 10.08% (n = 201) experienced post-index aspiration, LRTI, and RF, respectively. Significant predictors for aspiration were cough [3.39 (1.82–6.29)], dysphagia [3.04 (1.86–4.99)], LRTI [2.34 (1.22–4.51)], and neurological disorders (i.e., epilepsy/convulsions) [1.77 (1.18–2.66)]; LRTI were respiratory disorders [4.06 (2.63–6.27)], RF [3.02 (1.65–5.53)], neurological disorders [1.57 (1.07–2.29)], infections [1.69 (1.04–2.80)], and gastrointestinal disorders [1.57 (1.04–2.37)]; RF were LRTI [4.70 (2.58–8.58)], respiratory disorders [3.38 (2.23–5.13)], dysphagia [2.73 (1.73–4.31)], gastrointestinal disorders [2.09 (1.40–3.10)], musculoskeletal disorders [1.86 (1.01–3.40)], and neurological disorders [1.69 (1.16–2.45)]. Confirmartory models showed similar results.ConclusionBaseline neurological and respiratory disorders were common predictors of aspiration, LRTI, or RF. Additional predictors included gastrointestinal disorders for LRTI and RF; and musculoskeletal disorders for RF only. These real-world findings can help inform evidence based clinical decision-making for management of RTT.